Venezuelan Higher Education: The Chavez Revolution - Levy, Daniel (International Higher Education, 2011)
Hugo Chavez's clash with Venezuelan higher education is a vivid present-day example of a history of confrontation between leftist, populist regimes and higher education in Latin America. Chavez has transformed the public sector through creation and expansion of new universities. Chavez's policies have alienated the country's private institutions of higher education. Both public and private universities are reduced in importance.